VEDANADHYAYA: A CRUCIAL CONTRIBUTION OF KASHYAP SAMHITA IN PEDIATRIC CLINICAL EXAMINATION (International Journal of Ayurveda and Pharma Research, 2016)
The field of Ayurveda is broadly divided into eight parts. Kaumarbhritya refers to the science of diseases and care of children, right from conception till adolescence. Kashyap samhita is undoubtedly the pioneer text in this branch of Ayurveda. The text is divided in various sections (sthanas) of which Vedanadhyaya is twenty fifth chapter in Sutra sthana. It concerns the symptomalogy of various diseases in children and serves as a great guidance for pediatric examination and diagnosis as children are unable to narrate their symptoms themselves. The present article reviews the original text of the chapter and critically analyses it in light of contemporary medical science. It is noticeable that Acharya Kashyap has included a wide range of diseases pertaining to various systems like skin, ENT, gastro-biliary, hematology and urinary system and has also included the Bal grahas. The symptoms described are accurate and reasonable in contemporary scientific era also. Thus, a thorough study of Vedanadhyaya is essential for proper understanding of Ayurvedic perspective of pediatric illness and their common demarcating symptoms. It reinforces the view that children are not miniature adults and diseases in pediatric population have distinct features and need to be understood separately.